Mathematical model of feet temperature - Bento, David (2013)
In this work it is consider the problem of finding the best approximation to characterize the feet temperature distribution. For this study it was consider the nonlinear least squares technique, combined with penalty method, to identify the function that approximate better the data obtained through thermographic images. The preliminary results indicate that the best function approximation is based on trigonometric sums.